From individuals to settlement patterns. - Duering, A (2017)
This thesis describes and contextualises the Population & Cemetery Simulator (PCS), which represents agent-based demographic modelling software that can be used to model living populations based on archaeological and historical data as well as their cemeteries. The data used by the PCS are demographic in nature, e.g. age and sex data generated by osteoarchaeologists from excavated cemeteries or historical demographic data. This thesis seeks to provide a methodological foundation for modelling the demographics of archaeological populations. It focusses on case studies using data from early medieval Anglo-Saxon (South England) and Alamannic (South Germany) cemeteries, although excursions into neighbouring periods and regions are included as validation studies. The case studies show how the PCS can be used in archaeological research and the software is presented as a solution to various problems caused by the difference between the living population and the ‘dead’ cemetery data in archaeology.